A Luminescent 1D Silver Polymer Containing [2.2]Paracyclophane Ligands - Mackenzie, Campbell F. R.; Delforce, Lucie; Rota Martir, D.; Cordes, David B.; Slawin, Alexandra M. Z.; Zysman-Colman, Eli (Frontiers in Chemistry, 2021)
[2.2]Paracyclophane scaffolds have seen limited use as building blocks in supramolecular chemistry. Here, we report the synthesis and characterization of a 1D coordination polymer consisting of silver(I) ions bound to a [2.2]paracyclophane scaffold functionalized with two 4-pyridyl units. The structure of the polymer has been determined from single crystal X-ray diffraction analysis and reveals two different silver coordination motifs that alternate along the 1D coordination polymer. The coordination polymer exhibits strong blue and sky-blue fluorescence in solution and in the crystalline solid state, respectively.